Law among nations an introduction to public international law - Von Glahn, Gerhard 1911- (Routledge is an imprint of the Taylor & Francis Group, an informa business, 2017)
Updated in its 10th edition, Law Among Nations explains issues of international law by tracing the field's development and stressing key principles and processes. Offering a more accessible alternative to casebooks and historical commentaries,this comprehensive text eliminates the need for multiple books by combining discussions of theory and state practice with excerpts from landmark cases